2004
DOI: 10.1007/s00018-004-4122-z
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylglucosaminyltransferase V modifies the signaling pathway of epidermal growth factor receptor

Abstract: Transfection of sense cDNA of N-acetylglucosamyltransferase V (GnTV-S) into human H7721 hepatocarcinoma cells resulted in an increase in the N-acetylglucosaminebeta1,6mannosealpha1,3- branch (GnT-V product) on the N-glycans of epidermal growth factor (EGF) receptor (EGFR), and promotion of its EGF binding and tyrosine autophosphorylation, but showed little effect on the expression of EGFR protein. The phosphorylation at T308, S473 and tyrosine residue(s) and the activity of protein kinase B (Akt/PKB) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The result indicated that the structure of N-glycans in intracellular glycoproteins was altered generally due to the repression of GnT-V. It was consistent with the change of structure of N-glycans on GnT-V-AS/7721 cell surface in the previous studies [11][12][13].…”
Section: Inhibition Of N-glycans Synthesis N-glycans Structure Altersupporting
confidence: 89%
See 3 more Smart Citations
“…The result indicated that the structure of N-glycans in intracellular glycoproteins was altered generally due to the repression of GnT-V. It was consistent with the change of structure of N-glycans on GnT-V-AS/7721 cell surface in the previous studies [11][12][13].…”
Section: Inhibition Of N-glycans Synthesis N-glycans Structure Altersupporting
confidence: 89%
“…The previous studies also found that the fuction of the glycoproteins on cell surfaces was changed for abnormal quantity of GnT-V products, which influenced the pathways or mechanisms associated with cancer progress and metastasis potential [8,9,12,13]. However the effects of altering GnT-V expression or activity on glycans structures as well as functions of intracellular N-glycoproteins have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…L 4 -PHA lectin blotting revealed that the major target glycoproteins of GnT-V in mucinous ovarian carcinoma were 60-200 kDa in molecular size. Previous reports indicated several specific substrates for GnT-V glycosylation and changes in the biological characteristics of cancer cells; matriptase (21), lamp-1 (22), N-cadherin (23), ·5ß1-integrin (14,16), and epidermal growth factor receptor (EGFR) (24). In these substrates, ·5ß1-integrin is a protein heterodimer of 150 and 130 kDa, and is associated with migration.…”
Section: Discussionmentioning
confidence: 99%